Concentrations of selected heavy metals in placental tissues and risk for neonatal orofacial clefts. (November 2018) - Pi, Xin; Qiao, Yiran; Wei, Yihui; Jin, Lei; Li, Zhiwen; Liu, Jufen; Zhang, Yali; Wang, Linlin; Liu, Yaqiong; Xie, Qing; Ren, Aiguo
Abstract: Orofacial clefts (OFCs) have multifactorial etiologies. Prenatal exposure to heavy metals can induce OFCs in animal models, but evidence from studies of human subjects is scarce. We examined whether concentrations of mercury (Hg), cadmium (Cd), lead (Pb), and arsenic (As) in placental tissues are associated with risk for OFCs in offspring. This population-based case-control study included 103 newborns affected by OFCs with available placental tissues and 206 controls randomly selected from 509 non-malformed newborns with available placenta samples, recruited in five rural counties in northern China. Sociodemographic information was collected using a structured questionnaire in face-to-face interviews. The concentrations of Hg, Cd, Pb, and As in placental tissues were analyzed using an inductively coupled plasma-mass spectrometry in helium mode. The median concentrations of Hg (7.4 ng/g), Cd (57.1 ng/g), and Pb (96.1 ng/g) were all statistically significantly higher in OFC cases than in controls (Hg 5.5 ng/g, Cd 38.6 ng/g, and Pb 67.9 ng/g, respectively); no differences were observed between the two groups in median concentrations of As. Concentrations above the median for all subjects were associated with a 2.33-fold (95% confidence interval [CI] 1.33–2.09) increased OFC risk for Cd and a 3.08-fold (95% CI 1.74–5.47) increased risk for Pb. The risk for OFCs increased with concentration tertiles, with an adjusted odds ratio of 3.06 (95% CI 1.36–6.88) for the second tertile and 8.18 (95% CI 6.64–18.37) for the highest tertile of Cd, and 3.88 (95% CI 1.78–8.42) for the second tertile and 5.17 (95% CI 2.37–11.29) for the highest tertile of Pb. The association between Hg concentration and OFC risk was borderline nonsignificant after adjusting for confounding factors. Prenatal exposure to Cd and Pb, as reflected by their concentrations in placental tissues, is associated with an increased risk for neonatal OFCs. Graphical abstract: Image 1 Highlights: Higher concentrations of Cd and Pb in placental tissues were associated with increased risks for OFCs in offspring. The association between Cd and Pb concentrations in placental tissues and OFC risk showed a dose–response pattern. The association between Hg concentration in placental tissues and OFC risk was borderline nonsignificant. No association between As concentrations in placental tissues and OFC risk was observed.